New graduate nurses' clinical safety knowledge by the numbers. (22nd July 2019) - Murray, Melanie; Sundin, Deborah; Cope, Vicki
Abstract: Aim: To explore new graduate registered nurses' knowledge and attitudes concerning medical error and patient safety, during their first 6 months of professional practice. Background: New graduate registered nurses demonstrate basic skills and levels of performance due to limited exposure and experience in actual situations. There is a concern held for their clinical reasoning skills required to recognize patient deterioration, posing a threat to patient safety. Methods: An online questionnaire was used to survey new graduate registered nurses at three time points during graduate nurse programmes between August 2016 and February 2018. Results: A decrease in self‐reported knowledge and attitudes regarding medical errors was noted over the three time points. These results indicate initial confidence in theoretical knowledge and attitudes upon completion of undergraduate education, and prior to commencing professional practice. Conclusion: Results suggest that a theory practice gap persists with respect to medical error for transitioning new nurses. Impact for Nursing Management: New nurses lack confidence around compromised patient safety situations and a knowledge gap around actions related to medical error. Nurse managers and educators should be made aware of this gap to implement strategies to decrease risk during novice nurse transition.